2013
DOI: 10.1111/acer.12292
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of mGluR5 Antagonism During Binge Drinking on Subsequent Ethanol Intake in C57BL/6J Mice: Sex‐ and Age‐Induced Differences

Abstract: Background Binge ethanol (EtOH) intake during adolescence leads to an array of behavioral and cognitive consequences including elevated intake of EtOH during adulthood, with female mice showing greater susceptibility than males. Administration of the metabotropic glutamate receptor 5 (mGluR5) antagonist 3-((2-Methyl-1,3-thiazol-4-yl)ethynyl)pyridine (MTEP) has been shown to reduce EtOH self-administration in adult male mice, but little is known about its effect on female and adolescent mice. Methods MTEP (0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Thus, the sex differences in the binge alcohol-induced down regulation in mGlu5 mRNA and protein might differentially alter the expression of multiple genes beyond those implicated in glutamatergic signaling. Related to this point, female mice were sensitive to the ability of an mGlu5 antagonist to decrease binge alcohol consumption (Cozzoli et al, 2014a), but they were insensitive to the ability of an antagonist of a molecule in the PI3K signaling cascade (i.e., rapamycin; mTOR inhibitor) to decrease binge drinking (present findings). These findings indicate that in female mice, an alternate signaling pathway that is independent of PI3K and that links group 1 mGlus to transcriptional changes in the nucleus (i.e., protein kinase A, calcium calmodulin dependent protein kinase, or mitogen-activated protein kinase (MAPK); see Wang and Zhuo, 2012) is influenced by repeated binge alcohol consumption.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, the sex differences in the binge alcohol-induced down regulation in mGlu5 mRNA and protein might differentially alter the expression of multiple genes beyond those implicated in glutamatergic signaling. Related to this point, female mice were sensitive to the ability of an mGlu5 antagonist to decrease binge alcohol consumption (Cozzoli et al, 2014a), but they were insensitive to the ability of an antagonist of a molecule in the PI3K signaling cascade (i.e., rapamycin; mTOR inhibitor) to decrease binge drinking (present findings). These findings indicate that in female mice, an alternate signaling pathway that is independent of PI3K and that links group 1 mGlus to transcriptional changes in the nucleus (i.e., protein kinase A, calcium calmodulin dependent protein kinase, or mitogen-activated protein kinase (MAPK); see Wang and Zhuo, 2012) is influenced by repeated binge alcohol consumption.…”
Section: Discussionmentioning
confidence: 61%
“…Recent work found that mGlu5 antagonism decreased binge alcohol consumption in adult and adolescent male and female C57BL/6J mice, but that sex and age differences existed in the consequence of mGlu5 antagonism on later alcohol intake after a period of abstinence (Cozzoli et al, 2014a). Based on this result and reports that alcohol consumption in adolescent rodents can increase alcohol intake during adulthood (e.g., Broadwater et al, 2013; Moore et al, 2010; Strong et al, 2010), it is possible that male and female adult and adolescent mice have similar sensitivity to mGlu5 antagonists at the receptor level while the signaling downstream of mGlu5 might differ.…”
Section: Introductionmentioning
confidence: 99%
“…This study examined the biological implication of sexually divergent changes in the effect of repeated binge drinking on signaling molecules downstream of mGlu5 in adult male and female C57BL/6J mice (Figure 2A). Initial studies determined that the mGlu5 antagonist MTEP [3-((2-methyl-1,3-thiazol-4-yl)ethynyl)pyridine] was equally effective to decrease binge ethanol intake in male and female mice (Figure 2B), but that later ethanol intake after a period of abstinence was increased in females and unaltered in males (Cozzoli et al, 2014a). Thus, it is possible that male and female mice have similar sensitivity to mGlu5 antagonists at the receptor level while the signaling downstream of mGlu5 might differ between the sexes.…”
Section: Examples Of Sex Differences In Alcohol Researchmentioning
confidence: 99%
“…Values are the mean ± SEM for the number of animals on the figure. **p<0.01 versus respective saline group; adapted from (Cozzoli et al, 2014a). Panel C: Intra-accumbens rapamycin dose-dependently decreased binge ethanol intake during a 30-min binge session in male but not female mice, with a 28% decrease in binge ethanol intake following the 100 ng/side dose in male mice.…”
Section: Figurementioning
confidence: 99%
“…One of a handful of drugs currently approved to treat ethanol use disorders, acamprosate acts partly by blocking NMDA/metabotropic glutamate receptor (mGluR) signaling, and systemic administration significantly reduced DID ethanol intake in male B6 mice (Gupta et al, 2008). Systemic administration of mGluR5 antagonists reduces binge-like ethanol intake across multiple paradigms and mouse genotypes (Gupta et al, 2008; Tanchuck et al, 2011), however, a recent investigation suggests that their efficacy may be influenced by age and sex (Cozzoli et al, 2014b). Local infusion of an mGluR5 antagonist directly into the nucleus accumbens shell has also been shown to mirror this effect (Cozzoli et al, 2009).…”
Section: Mechanisms Of Binge-like Alcohol Consumptionmentioning
confidence: 99%